Follicular dynamics during the pre-ovulatory and subsequent first follicular wave stages affect the pregnancy outcome in Japanese Black cows - Tsumugi YOSHIYAMA; Tomomi KANAZAWA; Toru TAKAHASHI (The Society for Reproduction and Development, 2021)
The diameters of the pre-ovulatory follicles (PF) and the largest follicle during the subsequent first follicular wave (W1LF), and plasma estradiol-17β (E2) concentrations were monitored on Days 0, 1, 3, 5, and 7 (ovulation = Day 1). Pregnancy was diagnosed on Day 30. Cows were classified into two groups according to the location of the dominant follicle ipsilateral (IG) or contralateral (CG) to the corpus luteum on Day 7. From Days 3 to 7, some follicles that had been determined as the subordinate in the previous examination exceeded the W1LF located in the opposite ovary in terms of the diameter. These were defined as switching (SW), whereas others were defined as non-switching (NSW). The diameter of PF was significantly smaller in pregnant (P) animals than in non-pregnant (NP) animals. The plasma E2 concentration on Day 0 was significantly higher in P animals than in NP animals and tended to be higher in NSW than in SW. In addition, plasma E2 concentrations around Days 3 to 7 tended to be higher in P animals of NSW than in NP animals of SW. The conception rates did not differ between IG and CG but were significantly higher in NSW than in SW. In the IG group, the conception rate tended to be higher in NSW than in SW.